2016
DOI: 10.4103/0301-5742.179944
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of frontal sinus as a growth predictor in horizontal, vertical, and average growth pattern in children from 8 to 11 years: A cephalometric study

Abstract: The growth pattern is influenced genetically, environmentally, and therapeutically. These have long been considered as vital factors in determining the success or failure of orthodontic treatment. [1][2][3][4] The ability to predict craniofacial growth pattern accurately improves the reliability of treatment planning and long-term success. [5][6][7] It is, therefore, necessary for the orthodontist to evaluate the growth pattern meticulously before initiating treatment in growing individual.Literature has given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Based on a literature research performed on Pubmed, Scopus and EbSco by the authors it was evinced that there are a limited number of papers [ 26 , 27 ] investigating the relationship between frontal sinus size and cephalometric characteristics performed with three-dimensional imaging technique. Most of the researches have been performed using bidimensional radiographs such as lateral cephalograms and posteroanterior radiogram [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a literature research performed on Pubmed, Scopus and EbSco by the authors it was evinced that there are a limited number of papers [ 26 , 27 ] investigating the relationship between frontal sinus size and cephalometric characteristics performed with three-dimensional imaging technique. Most of the researches have been performed using bidimensional radiographs such as lateral cephalograms and posteroanterior radiogram [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The typical findings in subjects with thalessemia are a class II skeletal pattern, short cranial base length, short cranial length, short mandible, increased anterior and reduced posterior vertical dimensions and severe facial disfigurement as narrated by Alhaija et al 21 Bone age was delayed in protein energy malabsorption and males were affected more than females in accordance with studies of Tanner et al 22 and Frisancho et al 23 Malnutrition affected the maturation of the skeleton more than the teeth as confirmed by Steward et al 18 and Garn et al 19 According to a recent study conducted by Nathani et al, 24 frontal sinus can also be used as predictor for evaluation of growth patterns. In fact it has been found to be more reliable than maxillary sinus in assessment of different types of malocclusions.…”
Section: Discussionmentioning
confidence: 62%
“…This is because of the poor transmission of occlusal forces along the trajectories of nasal pillars and reduced muscular activity. The increased frontal sinus size was associated with a reduced inclination of the anterior cranial base, increased anterior facial height, and gonial angle [ 14 - 16 ]. Goymen et al [ 17 ] could not find any relevance between the growth pattern and the size of the sinuses.…”
Section: Discussionmentioning
confidence: 99%